2015
DOI: 10.1590/0001-3765201520140187
|View full text |Cite
|
Sign up to set email alerts
|

Does ethnic ancestry play a role in smoking?

Abstract: The higher proportion of smokers among Black people in Brazil has been attributed to socioeconomic disparities, but genetic factors could also contribute for this finding. This study aimed at investigating associations between smoking status with genetically defined ethnic ancestry and socioeconomic features in Brazilians. Blood samples were collected from 448 volunteers (66.7% male; age: 37.1±11.4 years) classified as current smokers (CS: 60.9%), former smokers (FS: 8.9%) and never smokers (NS: 30.1%). Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
5
1
Order By: Relevance
“…However, the child's school experience and the socioeconomic status of the family also contribute to this diversity. Similarly, in a study by Souza et al (2015), the use of genetic markers for characterization of ancestry background strongly suggests that socioeconomic disparities, and not ethnicity, are the main determinants of higher smoking rates among blacks in Brazil.…”
Section: Introductionmentioning
confidence: 98%
“…However, the child's school experience and the socioeconomic status of the family also contribute to this diversity. Similarly, in a study by Souza et al (2015), the use of genetic markers for characterization of ancestry background strongly suggests that socioeconomic disparities, and not ethnicity, are the main determinants of higher smoking rates among blacks in Brazil.…”
Section: Introductionmentioning
confidence: 98%
“…[20][21][22] Only one study has evaluated FAP families in the Brazilian population, 23 which has a tri-hybrid genetic background specifically, encompassing Native American, European, and African ancestries. 24 Although we have not inferred the ancestry of our cohort, De Souza et al 25 have previously evaluated the ancestry components of patients admitted at the same hospital where we collected our samples, and showed that these patients had approximately 85% European ancestry, 10% African, and 4% Native American ancestry. These proportions are in agreement with studies that evaluated the ancestry of different cohorts, confirming the admixed unique background of the Brazilian population.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out in their paper (Souza et al 2015), some studies indicate that white Americans are more likely to smoke than the black population (e.g., Ward et al 2002). In Brazil, however, the opposite has been shown: the tendency is that the white population smokes less than others (e.g., INCA 2011).…”
mentioning
confidence: 96%
“…In this issue of the AABC, we are publishing a contribution that is a little bit different from previous ones. Souza et al (2015) have investigated the relation between ethnic ancestry and the habit of smoking.…”
mentioning
confidence: 99%
See 1 more Smart Citation